Revenue Potency of University of Mataram Through Cash Management - Suhaedi, wirawan; Sasanti, Elin Erlina (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2020)
University of Mataram is one of higher education entities with a Public Service Agency (BLU) status. As a BLU entity that has flexibility in financial management, the University of Mataram is expected to optimize its potential to generate revenue. One potential that can generate substantial income is by utilizing the cash owned by the University of Mataram for investment. This study aims to identify the potential revenue that can be generated by the University of Mataram. This research was conducted to provide alternative investments through BLU cash management in order to generate more optimal income for the University of Mataram. BLU entity could invest their cash as long as it does not interfere with the operational activities of the university. This research was conducted by determining the amount of BLU funds that have not been used (idle cash) for operational activities, which can be used for investment. The results of this study indicate that University of Mataram could potentially optimize their BLU revenue through cash management up to Rp. 8.482.681.740,- per year.The average revenue from the placement of cash in bank is currently Rp 3.613.488.324,-, which indicate that there is still an untapped revenue potential of Rp 4.869.193.416. This potential revenue could be obtained by utilizing idle cash from current accounts to time deposits